Pengaruh Lingkungan Kerja, Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Guru di Lembaga Pendidikan Terpadu Nurul Ilmi Banyuasin - Siti Fatimah J; Luis Marnisah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine whether the Work Environment, Work Discipline and Work Motivation have an effect on Teacher Performance. This research was conducted at the Nurul Ilmi Banyuasin Integrated Education Institution. The research method used in this study is a quantitative method. The population in this study were all teachers at the Nurul Ilmi Banyuasin Integrated Education Institution, while the number of samples used was 85 respondents using saturated sampling techniques. The instrument in this study used a questionnaire. The data analysis method in this study used descriptive statistical tests, instrument quality tests, classical assumption tests, multiple regression analysis and hypothesis tests. Based on the results of this study, it is known that the variables of the work environment, work discipline and work motivation have a significant effect on teacher performance at the Nurul Ilmi Banyuasin Integrated Education Institution with a calculated F value of 34.519 while the F table value is 2.717 thus the calculated F 34.519> F table 2.717. The results of the Determination Test show that the R-Square value is 0.561 or 56.1%, indicating that the variables of Work Environment, Work Discipline and Work Motivation are able to influence Teacher Performance by 56.1%, the remaining 100% - 56.1% = 43.9% is explained by other variables or factors that are not studied. In the work environment and work discipline as well as the existence of good and high work motivation will have a good impact on teachers in carrying out their duties and responsibilities so that it will affect better teacher performance.